One drawing a day : a 6-week course exploring creativity with illustration and mixed media - Lawlor, Veronica (Quarry Books, 2011)
"Through 46 daily exercises which make up a complete 6-week course, you will keep your artistic skills sharp and your imaginations fertile by doing One Drawing A Day. Each spread in the book features a beautiful drawing by one of 8 professional illustrators, with a description and comments by the illustrator as well as a companion exercise. Each exercise includes suggestions for various mediums or mixed-media solutions, advice on how to approach and execute the drawing, as well as professional tips. The book also includes exercises designed to spark new ideas and increase creativity"--